Artificial Intelligence Maturity Assessment in Leadership at Higher Education: A Case Study - Samiya Al-Hinaai; Khalfan Al-Hijji; Faten Hamad (Journal of Techno-Social, 2024)
There is a growing interest in artificial Intelligence (AI) as a research topic. Adapting to AI technologies has become essential for educational institutions, specifically educational leaderships in order to embrace AI trends in enhancing leadership practices. This study comes in response to the increased discussions of AI implementing in education, which has created the need for AI Maturity Model in education to help educational institutions assess their progress in AI adaptation. This paper investigated how are the leaderships at college of Arts and Social Sciences Departments in Sultan Qaboos University (SQU) in Oman, as a case study, has adapted AI technologies throughout AI Maturity lens. The study aims to assess the college AI Maturity level and the qualitative approach was used to collect the data via semi-structured interviews with the college’s heads and decision makers. The results showed that the leaderships at the college are updated with the AI developments, however, the academic departments are still in their early stages of using AI technologies as AI is still an emerging topic. The leaderships have good awareness of the importance of integrating AI in teaching-learning process at higher education institutions’ level and the effects of adapting such technologies. Through in-depth interviews and the qualitative data analysis, one key finding was that College of Arts and Social Science at SQU is establishing good infrastructure for AI revolution at higher education according to the AI 5Ds cycle as there are some significant efforts to raise the awareness of the importance and role of AI in higher education and some individual AI implementations. However, more clear plans and work are needed for the move to the next phases of applying AI technologies in HE